Trust Studies of Zakat Institutions: A Systematic Review for Future Research Direction - Azhar Alam; Ririn Tri Ratnasari; Muhamad Nafik Hadi Ryandono; Ari Prasetyo; Estina Rahmawati (International Journal of Emerging Issues in Islamic Studies, 2023)
This study systematically reviewed the literature on trust-related publications in zakat institutions. This study revealed the development of the study of trust in zakat institutions, the thematic classification of the study, and discussions on the direction of future research development. This study adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) system in screening the articles that were the subject of the study. From 415 zakat study documents indexed by the Scopus database, this study selects all articles and leaves 24 studies that make trust in zakat institutions the primary study material.The results show an increasing trend in the number of publications discussing trust in zakat institutions in recent years. This study also classified the findings from empirical research and conceptual models in the factors that shape trust in zakat institutions and the influence of faith on zakat behavior. This study also mapped out qualitative study findings that explain the sources of public distrust of zakat institutions and the solutions offered. This research is a pioneer in the discussion of literature systematically related to the research of trust in zakat institutions. This study also discussed potential research develop a survey of trust in zakat institutions.